Population genetics - Cox, Murray P. (Henry Stewart Talks, 2011)
Studying human evolution using population genetics, The history of population genetics, Demographic models, DNA datasets, Example genealogies, Calculating summary statistics (number of polymorphisms; average pairwise difference; Tajima's D), Inference, Statistical significance, Current work in population genetics, Population genetics' studies in Africa
Updated at 2014/11/05